Canine Uncanny Zone: Review of: Adrienne L. McLean, ed., Cinematic Canines: Dogs and Their Work in the Fiction Film; Ann-Janine Morey, Picturing Dogs, Seeing Ourselves: Vintage American Photographs; Philip Howell, At Home and Astray: The Domestic Dog in Victorian Britain - Young, Elizabeth (Humanimalia, 2016)
Adrienne L. McLean, editor, Cinematic Canines: Dogs and Their Work in the Fiction Film. New Brunswick, NJ: Rutgers University Press, 2014.  272 pp. $90.00 hc; $27.95 pd; $27.95 e-book.Ann-Janine Morey, Picturing Dogs, Seeing Ourselves: Vintage American Photographs.  University Park, PA: The Pennsylvania State University Press, 2014. 228 pp. $34.95 hc.Philip Howell, At Home and Astray: The Domestic Dog in Victorian Britain. Charlottesville, VA: University Press of Virginia, 2015. 252 pp. $39.50 hc; $39.50 e-book.